2009
DOI: 10.1111/j.1365-2222.2008.03124.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐allergic effects of PG102, a water‐soluble extract prepared from Actinidia arguta, in a murine ovalbumin‐induced asthma model

Abstract: PG102 may have potential as a safe and effective reagent for the prevention or treatment of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…These in vivo findings were also strongly supported by the data from various in vitro cell culture experiments [5, 7]. All these results suggested that PG102 might have preventive or therapeutic effects on a broad range of allergic diseases.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These in vivo findings were also strongly supported by the data from various in vitro cell culture experiments [5, 7]. All these results suggested that PG102 might have preventive or therapeutic effects on a broad range of allergic diseases.…”
Section: Discussionsupporting
confidence: 76%
“…We have previously shown that PG102 could regulate the expression of IgE and Th1 and Th2 cytokines involved in the allergy pathogenesis, using the OVA-sensitized mouse, NC/Nga dermatitis mouse, magnesium-deficient hairless rat and OVA-induced asthmatic mouse models [5,6,7]. These in vivo findings were also strongly supported by the data from various in vitro cell culture experiments [5, 7].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…PG102, an aqueous extract from Actinidia arguta (26), is an example exhibiting such an activity. White rose fetal extract of Rosa rugosa root (27), procyanidin C1 from apple (28), and hot water extract of Cydonia oblonga (29) have shown potential in inhibiting chemical-induced animal model or NC/Nga mice.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that a water-soluble extract prepared from Actinidia arguta improved asthmatic symptoms via the down-regulation of IgE in mouse (5). Lee et al found that resveratrol, which has been identifi ed in various fruit and vegetable extracts, inhibited Th2-type cytokines such as IL-4 and IL-5, and suppressed airway hyperresponsiveness, eosinophilia, and mucus hypersecretion in an asthmatic mouse model (6).…”
mentioning
confidence: 99%